Role of microRNAs in spermatogenesis - S. A. Rudneva; A. A. Khachenkova (Андрология и генитальная хирургия, 2016)
Male germ cells have a complex transcriptome. In addition to proteincoding messenger RNAs, many noncoding RNAs, including microRNAs (miRNAs), are produced. The miRNAs are important regulators of gene expression. They function mainly post-transcriptionally to control the stability or translation of their target messenger RNAs. The miRNAs are expressed in a cell-specific manner during spermatogenesis to participate in the control of each stage of male germ cell differentiation. Clinical studies have exploited the well-defined expression profiles of miRNAs, and human spermatozoal or seminal plasma miRNAs have been explored as potential biomarkers for male factor infertility.